A Trust Evaluation Model for E‐Learning Systems. (25th March 2014) - Tan, Wenan; Chen, Senbo; Li, Jingxian; Li, Lingxia; Wang, Tong; Hu, Xiaoming; Xu, Li Da
<x xml:space="preserve">Abstract</x> In recent years, electronic learning (e‐learning) has become an increasingly important method in education. Under the environment of Internet of Things, it has been predicted that e‐learning systems will grow at an even greater pace. Therefore, it is crucial to find a simple and effective evaluation method to assess user trust in e‐learning systems. In this paper, we present an evaluation model based on user trust cloud and user capability for trusted e‐learning. A user trust cloud model is proposed to assess a user's subjective trust, and a capability matrix method is introduced to assess a user's objective trust. The proposed model has been implemented for trust management in e‐learning systems. Experimental results show that the proposed trust evaluation model is useful and applicable to the user trust assessment in complex e‐learning systems. Copyright © 2014 John Wiley & Sons, Ltd.